COMPLICATIONS ASSOCIATED WITH RETROMANDIBULAR TRANSPAROTID APPROACH FOR CONDYLAR FRACTURE PLATING AT MAXILLOFACIAL SURGERY UNIT HAYATABAD MEDICAL COMPLEX, PESHAWAR; A CLINICAL AUDIT - Rehman Khattak, Yasir; Shah, Khadim; Waqas, Muhammad; Rehman, Summayya; Mushtaq, Muhammad (Khyber Journal of Medical Sciences, 2023)
Purpose: This study was designed to evaluate postoperative complications associated with open reduction and rigid internal fixation (ORIF) with RMA for fractures of the mandibular condyles. Materials and Methods: This retrospective study was undretaken at the Department of Dental and Maxillofacial Surgery, Hayatabad Medical Complex, Peshawar, Pakistan for the period of January to December, 2021, of patients with condylar fractures requiring ORIF via RMA. The inclusion criteria were patients with mandibular condylar fractures, underwent ORIF with RMA and minimum postoperative follow up of six months. The predictive variables included age, gender, address, etiology, fracture side and location, temporomandibular joint (TMJ) Pain on visual analog scale (VAS), malocclusion and facial asymmetry. Results: Of the total 68 medical records retrieved, only 27 cases met the inclusion criteria. The male to female ratio of the patients was 1.25: 1. The causes of the trauma were road accident (48%), accidental falls (30%) and active physical violence (22%). Isolated condylar fractures were noted in 15% (4 patients) cases, while 85% (23 patients) presented with other mandibular fractures. The postoperative complications assessed were facial nerve weakness, salivary (parotid) fistula, Frey’s syndrome, scar formation and restriction of lateral movements of the jaw. Overall, the postoperative complications were temporary and resolved with time. The improvement in postoperative mandibular movements were statistically significant (p < 0.05), as compared to preoperative status. Conclusions: The RMA provides the ease of access to the condylar fracture site, sufficiently clear exposure and ease of fixation, while the associated postoperative complications resolve with time.